Microbusinesses and Occupational Stress: Emotional Demands, Job Resources, and Depression Among Korean Immigrant Microbusiness Owners in Toronto, Canada - Il-Ho Kim; Samuel Noh; Cyu-Chul Choi; Kwame McKenzie (Korean Society for Preventive Medicine, 2019)
Objectives While occupational stress has long been a central focus of psychological research, few studies have investigated how immigrant microbusiness owners (MBOs) respond to their unusually demanding occupation, or how their unresolved occupational stress manifests in psychological distress. Based on the job demands-resources model, this study compared MBOs to employees with regard to the relationships among emotional demands, job resources, and depressive symptoms. Methods Data were derived from a cross-sectional survey of 1288 Korean immigrant workers (MBOs, professionals, office workers, and manual workers) aged 30 to 70, living in Toronto and surrounding areas. Face-to-face interviews were conducted between March 2013 and November 2013. Results Among the four occupational groups, MBOs appeared to endure the greatest level of emotional demands, while reporting relatively lower levels of job satisfaction and job security; but MBOs reported the greatest job autonomy. The effect of emotional demands on depressive symptoms was greater for MBOs than for professionals. However, an inspection of stress-resource interactions indicated that though MBOs enjoyed the greatest autonomy, the protective effects of job satisfaction and security on the psychological risk of emotional demands appeared to be more pronounced for MBOs than for any of the employee groups. Conclusions One in two Korean immigrants choose self-employment, most typically in family-owned microbusinesses that involve emotionally taxing dealings with clients and suppliers. However, the benefits of job satisfaction and security may protect MBOs from the adverse mental health effects of job stress.